Anti-racism: totem and taboo – a review article. (July 2015) - Burnett, Jon
Against a backdrop of punishing austerity measures, the ascent of the neoliberal project and the undermining of multiculturalism, anti-anti-racism is seeing a renascence in the UK. This resurgent critique decries anti-racism as set against white working-class communities, argues that it exists to serve a liberal elite, and that it feeds into a multicultural dogma undermining western culture. Fear of the charge of racism, it is argued, prevents discussion and rational policy measures to manage immigration, race and identity. This review article examines three recent books embodying aspects of these claims, as well as showing how a liberal ceding of ground to the Right on the intersections of race and class ultimately bolsters its arguments.